Tipologi Moderasi Keagamaan: Tinjauan Tafsir al-Muni>r Karya Wahbah Az-Zuhaili - Azizatul Qoyyimah; Abdul Mu’iz (Pascasarjana IAIN Sultan Amai Gorontalo, 2021)
The purpose of this research is to investigate Wahbah Zuhaili's view of religious moderation in Tafsir al-Munir. This research used a qualitative approach with the type of library research. Wahbah az-Zuhaili defines moderate people as those who are led down the straight path, wasath (moderate, balanced) in all matters, able to balance the work of the world and the hereafter, upholding the truth solely and sincerely because of Allah SWT, and being able to give testimony correctly, honestly, objectively, fairly, impartially, and not tyrannically. Moderate Islam also places a high value on and pays close attention to moral and ethical goals, and believes that Islamic law is dynamic and adaptable to changing and increasingly complex times. In Islam, the implementation of moderate religious values includes honesty, compassion, flexibility, and deliberation.